Identification of Bottlenecks in Rod Slider Production Using Siemen Tecnomatix Plant Simulation - Tee, Boon Long; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2024)
The manufacturing industry has long strived to improve production line efficiency by reducing waste and costs while increasing profits. However, issues such as bottlenecks, underutilization of resources, and downtime could have improved overall manufacturing process efficiency. Hence, the present study aims to identify the bottlenecks and their efficiency on the existing rod slider production line. In this study, Tecnomatix Plant Simulation software was used to mimic the production line, where data were obtained utilising qualitative methodologies like interviews with the company’s CEO and firsthand observation of the manufacturing line. The present rod slider manufacturing has a bottleneck at CNC turning and milling, reducing production line efficiency by 20%. The suggested solution to optimise the present production line by using in-house processing reveals that the identified bottleneck may be removed or minimised by up to 12%. This increases the production line efficiency from 20% to 92.5%. The findings offer real strategies for enhancing effectiveness and optimising production processes by proactively identifying and resolving bottlenecks using various means.